Intersectional research on dementia care for post-migrants and ethnic minority groups: a scoping review - Altinok, Kübra; Güney, Seda; Yüceer, Bugse; Razum, Oliver; Roes, Martina (Frontiers in Dementia, 2025)
ObjectiveThe aim of this scoping review is to identify the range, extent and nature of evidence available in peer-reviewed and gray literature and to examine how the intersecting experiences and differences of post-migrants and ethnic minority groups influence preferences.MethodsThe Arksey and O’Malley methodological framework and the PRISMA-ScR for Scoping Reviews confirm the rigor of the scoping review. We systematically searched across electronic databases including PubMed, MEDLINE via Ovid, CINAHL, Scopus, Cochrane Library as well as gray literature between December 2023 and September 2024. We included the articles in English, German, and Turkish languages without any publication date restrictions. We analyzed the identified intersectional determinants of preferences using inductive content analysis.ResultsLimited studies focusing on the intersectional determinants of preferences of ethnic minority groups or post-migrants with dementia were found. After screening 1,404 studies, we identified 4 relevant papers through the search strategy. Additionally, we identified 18 records through hand-searching, gray literature, and reference list checks. In total, 22 articles were included in this review. Inductive content analysis allowed to reach six main-theme focusing on the preferences, which are preferences connected to informal care providers, expectations in nursing homes/care institutions, preferences of care setting, coping approaches and preferences, food preferences, and other daily preferences.DiscussionOur findings highlight the complexity of personal care preferences, showing that expectations and practices are shaped by cultural values, traditions, language barriers, immigration processes, shifting socioeconomic positions, and gender roles. The lack of attention to the preferences of the diverse groups and the limited support for their unique wishes and needs indicates a significant challenge in the health system. Caregiving choices and daily living are shaped by intersecting structural determinants and differences. However, there are still gaps in research, healthcare practices, and public awareness, making it harder to meet their preferences.Systematic review registrationRegistration DOI: https://doi.org/10.17605/OSF.IO/Z8T9H.